Brita Flou, Børge Kjær, Jytte Thorndahl m.fl.: Kolindsund - et stykke Djursland fortæller danmarkshistorie. (P. S. Johnsen, Grenå 1980). 213 s., ill. - Vedel-Smith, Henrik (Historie/Jyske Samlinger, 1987)
-